PIK3CA-related overgrowth: silver bullets from the cancer arsenal?. Issue 4 (April 2022) - Madsen, Ralitsa R.; Semple, Robert K.
Abstract : Mutations that activate growth factor signaling often drive cancer growth. Many also arise in isolation, causing developmental growth disorders. PIK3CA, that encodes a catalytic subunit of phosphatidylinositol 3-kinase (PI3K), is a cardinal example of this paradigm. Recent exciting progress towards the key goal of cancer drug repurposing for PIK3CA-driven overgrowth is discussed.